2015
DOI: 10.1021/acs.nanolett.5b02489
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Thin-Film Supercapacitors with Ultrafast Charge/Discharge Based on N-Doped-Carbon-Tubes/Au-Nanoparticles-Doped-MnO2 Nanocomposites

Abstract: Although carbonaceous materials possess long cycle stability and high power density, their low-energy density greatly limits their applications. On the contrary, metal oxides are promising pseudocapacitive electrode materials for supercapacitors due to their high-energy density. Nevertheless, poor electrical conductivity of metal oxides constitutes a primary challenge that significantly limits their energy storage capacity. Here, an advanced integrated electrode for high-performance pseudocapacitors has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(76 citation statements)
references
References 76 publications
(113 reference statements)
3
73
0
Order By: Relevance
“…The Mn 2p 3/2 peak of all samples can be deconvoluted into three peaks as Mn 4+ (642.8 eV), Mn 3+ (641.8 eV), and Mn 2+ (640.7 eV). [1,36,37] The proportion of Mn 4+ peaks shows almost no change after PECVD process, demonstrating the phase stability in the PECVD process. [38] Moreover, chemical titration was used to further quantitatively confirm the average valence for Mn in different samples.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The Mn 2p 3/2 peak of all samples can be deconvoluted into three peaks as Mn 4+ (642.8 eV), Mn 3+ (641.8 eV), and Mn 2+ (640.7 eV). [1,36,37] The proportion of Mn 4+ peaks shows almost no change after PECVD process, demonstrating the phase stability in the PECVD process. [38] Moreover, chemical titration was used to further quantitatively confirm the average valence for Mn in different samples.…”
Section: Resultsmentioning
confidence: 95%
“…Supercapacitors which pose faster charge/discharge rates and higher power density are becoming hot topics of current research worldwide. [1][2][3][4] However, the practical application of supercapacitors has long been a challenge because of their limited energy density. Thus, focused on the voltage undertaken by structural modification through Na + deintercalation and intercalation and found that the potential of the Mn 3 O 4 can be extended to 1.3 V through this method.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al [185] demonstrated the superior cycling performance (97% after 5000 cycles) of the nanocomposite formed by N-doped carbon tubes and Au-doped MnO 2 nanoparticles. Fan et al [186] proposed a new composite of carbon nanotubes (CNTs)/graphene, composed of CNT pillars sandwiched between the graphene sheets that showed a specific capacitance as high as 385 F·g −1 .…”
Section: Nanocompositesmentioning
confidence: 99%
“…What is more, the flexible ASC exhibits an energy density of 0.776 mWh cm −3 at a power density of 9.859 mW cm −3 for a 2.0 V voltage window, as shown in Figure e. It also preserves 52 % of its energy density as the power density increases to 142.56 mW cm −3 . These values are higher than the values reported for other solid‐state SCs such as N‐doped‐CNTs//Au‐doped‐MnO 2 ASC (0.097 mWh cm −3 ), MnO 2 //Fe 2 O 3 ASC (0.55 mWh cm −3 ), VO x //VN ASC (0.61 mWh cm −3 ), MnO 2 @ZnO//reduced graphene oxide (RGO) ASC (0.234 mWh cm −3 ), TiO 2 @C NWs symmetrical supercapacitor (SSC; 0.011 mWh cm −3 ), and NiCo 2 O 4 @TiN SSC (0.061 mWh cm −3 ) . These results indicate that the flexible solid‐state ASC holds promise for use in portable energy‐storage systems.…”
Section: Resultsmentioning
confidence: 99%